After the Katowice climate summit: Building blocks for the EU climate agenda - Susanne Dröge; Vijeta Rattani (Stiftung Wissenschaft und Politik (SWP), 2019)
In Katowice, Poland, the 24th meeting of the Conference of the Parties (COP24) under the United Nations Framework Convention on Climate Change (UNFCCC) took place in December 2018. The parties adopted a rulebook for the implementation of the Paris Agreement, which was an urgent and necessary step to operationalise the climate regime that is taking effect from 2020 onwards. The COP also addressed short-term climate ambitions by finishing the Talanoa Dialogue, a platform dialogue including stakeholders from civil society for sounding out mitigation potential before 2020. The European Union (EU) and its member states are among the few global actors remaining with the means and determination to follow up on supporting the international climate agenda. Thus, in preparation of the 2019 September climate summit convened by the UN Secretary-General (UNSG), António Guterres, the EU will have to demonstrate its willingness to reduce emissions by upgrading short- and long-term targets and to support poor countries, politically and financially. The vulnerable developing countries rely on the EU and its member states as leaders and partners for the national implementation of the rulebook's technicalities. Not least, the EU has to focus on deepening cooperation with emerging countries and on raising awareness for climate change across policy fields.
Keywords: 320